Некоторые международно-правовые аспекты режима Арктики - Moskwa, Urszula (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the selected international aspects of Arctic legal regime. The author presents the Arctic as a land of special feature because of its location. The author focus on the selected law acts, regulating its status.